1998
DOI: 10.1071/pp98004
|View full text |Cite
|
Sign up to set email alerts
|

UV-B, red and far-red light regulate induction of the C4 isoform of NADP-malic enzyme in etiolated maize seedlings

Abstract: The induction of NADP-malic enzyme (NADP-ME) in maize (Zea mays) etiolated seedlings as a function of intensity and duration of exposure to UV-B radiation was investigated by measuring changes in activity and protein, as well as by levels of NADP-ME gene transcripts. Exposures to UV radiation from 2 to 60 min including photon flux densities of UV-B of 0.5–2 mmol quanta m-2 s-1 which are well below levels which occur naturally under full sunlight, caused an increase in Me gene mRNA and NADP-ME protein, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…We have recently shown that UV‐B radiation could induce NADP‐ME activity in both etiolated and green maize leaves (a C 4 plant) (Drincovich et al . 1998; Casati et al . 1998) and also in leaves of different cultivars of bean (a C 3 plant) (Pinto et al .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have recently shown that UV‐B radiation could induce NADP‐ME activity in both etiolated and green maize leaves (a C 4 plant) (Drincovich et al . 1998; Casati et al . 1998) and also in leaves of different cultivars of bean (a C 3 plant) (Pinto et al .…”
Section: Resultsmentioning
confidence: 99%
“…The NADP‐ME activity of etiolated maize seedlings was previously reported to be markedly increased above constitutive levels not only after exposure to PAR supplemented with UV‐B radiation but also by red light (Casati et al . 1998).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations